The application of ADAMS/CAR in vehicle engineering teaching. (2018) - Fan, Xiaobin; Sun, Yuankui
In order to improve the vehicle engineering professional courses teaching effect and students' learning interest, make up for the lack of investment professional experimental facility, high cost and danger of car experiment, it is necessary to introduce simulation software in professional teaching and experiment. In this paper, we first introduce the basic characteristics of the virtual prototype software ADAMS/CAR, the subsystem modelling method, especially the subsystem parameters measuring method. And then we introduce the subsystem and vehicle assembly simulation method, electronic control system co-simulation method and the results post-processing method. These provide important guidance for the theoretical and experimental teaching of professional courses, such as vehicle theory, vehicle design and vehicle system dynamics, etc.